Knowledge and skills of accredited social health activists in home based new-born care in a rural community of Northern India: an evaluative survey - Choudhary, Mangi Lal; Joshi, Poonam; Murry, Levis; Malhotra, Sumit; Shankar, Jeeva (International Journal Of Community Medicine And Public Health, 2020)
Background: Home based new-born care (HBNC) is a strategy implemented by the Government of India to overcome the problem of new-born deaths and reach the unreached new-borns in the community. Aim was to assess the knowledge and skills of ASHA workers and factors influencing the skills. Methods: In an observational study, a total of 48 accredited social health activists (ASHA) working under a primary health centre (PHC) were enrolled using a total enumeration sampling technique. A self-developed, pre-tested and validated tool based on home based new-born care was used for data collection. Results: Mean knowledge and skill scores of ASHA workers were 16.4±4.2 and 27.7±4.3 respectively. Nearly half of the ASHA workers had average knowledge, while two-thirds had good skills towards HBNC. Most of ASHA workers had shown good skills in measuring the temperature of new-borns, handwashing and count the respiration correctly, while less than 40% of ASHA workers performed weight recording correctly. Knowledge and overall skill scores of ASHA workers were positively correlated (r=0.58, p<0.001). Statistically significant associations were observed between the overall skills scores of ASHA workers and educational status, working experience and the last training attended on HBNC (p=0.001). Conclusions: Most of the ASHA workers had exhibited good skills, but were lacking scientific knowledge related to HBNC. There is need for having periodic re-orientation training for facilitating application of scientific knowledge to HBNC.